Neuropsychiatric Outcome of Children Born to Women With Systemic Lupus Erythematosus and Exposed in Utero to Azathioprine: A Case-Control Study - Lazzaroni, Maria-Grazia; Andreoli, Laura; Crisafulli, Francesca; Tamborini, Francesco; Debeni, Irene; Binda, Valentina; Nalli, Cecilia; Galli, Jessica; Fazzi, Elisa; Moroni, Gabriella; Franceschini, Franco; Tincani, Angela (Frontiers in Pharmacology, 2020)
Objective: The long-term outcome of children born to SLE mothers still represents a controversial topic in literature, with some studies reporting a possible increased prevalence of different neurologic and psychiatric diseases (NPD), including neurodevelopmental disorders (ND), and in particular learning disorders (LD). Different risk factors have been advocated, such as the in utero exposure to auto-antibodies and drugs, particularly Azathioprine (AZA). Methods: A case-control study was designed to compare pregnancies treated with AZA (cases) with those not treated with AZA (controls). All the pregnancies had been prospectively followed in 2 Italian centres. The match was based upon renal involvement, aPL status, maternal age at pregnancy (± 5 years) and child’s age at the time of the study (±2 years). SLE mothers were interviewed by a telephone survey, particularly focused on the presence of a certified NPD in their children ≥6 years of age. Results: Twenty-seven cases and 65 controls were similar in terms of demographic, immunological and clinical features, except for a higher rate of SLE flares during pregnancy in cases (22.2% vs 10.8%, p:0.191). The 92 children had a mean age of 14.0 years at the time of the survey; 11 had at least one NPD (12.0%). The frequency of each single NPD was similar to that of the general pediatric population and no association was found with either the in utero exposure to AZA, or other specific factors (auto-antibodies, disease activity, obstetric complications, prematurity). Conclusion: The long-term neuropsychiatric outcome of the children born to SLE mothers did not show neither an increased frequency of NPD as compared to the general pediatric population nor a specific pattern of NPD. The in utero exposure to AZA was not associated with the development of NPD in this case-control study of prospectively-followed pregnancies. NPD are complex conditions and large prospective studies are needed to capture the wide range of variables that may contribute to their development in the offspring of SLE women.